2017
DOI: 10.1192/bjp.bp.117.202259
|View full text |Cite
|
Sign up to set email alerts
|

Sleep loss as a trigger of mood episodes in bipolar disorder: Individual differences based on diagnostic subtype and gender

Abstract: BackgroundSleep loss may trigger mood episodes in people with bipolar disorder but individual differences could influence vulnerability to this trigger.AimsTo determine whether bipolar subtype (bipolar disorder type I (BP-I) or II (BD-II)) and gender were associated with vulnerability to the sleep loss trigger.MethodDuring a semi-structured interview, 3140 individuals (68% women) with bipolar disorder (66% BD-I) reported whether sleep loss had triggered episodes of high or low mood. DSM-IV diagnosis of bipolar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 35 publications
2
71
2
Order By: Relevance
“…This could explain why individuals with BD-I are more likely than those with BD-II to report sleep loss triggering episodes of high mood. 12 In contrast, increased genetic risk for insomnia in people with BD-II may reflect the known genetic associations between BD-II and depression. 52 Both depression and insomnia are associated with negative attentional biases 62 and are significantly genetically correlated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could explain why individuals with BD-I are more likely than those with BD-II to report sleep loss triggering episodes of high mood. 12 In contrast, increased genetic risk for insomnia in people with BD-II may reflect the known genetic associations between BD-II and depression. 52 Both depression and insomnia are associated with negative attentional biases 62 and are significantly genetically correlated.…”
Section: Discussionmentioning
confidence: 99%
“…4 Furthermore, reduced sleep duration, a symptom of manic episodes, has been implicated as a prodrome and trigger of mania. [10][11][12][13][14] These findings have initiated interventions that aim to improve wellbeing and reduce episode recurrence in BD by improving sleep. 15,16 An example is cognitive behavioural therapy for insomnia adapted for individuals with BD, with several randomised controlled trials piloted or currently in progress.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances are highly prevalent in bipolar disorder, and are often consequent to a reduced need for sleep in mania . Sleep disruption is a triggering factor for manic/hypomanic episodes in some vulnerable patients, or an exacerbating factor for depression in others . Sleep problems are also a hallmark of schizophrenia, including delays in falling asleep, difficulties in maintaining sleep, reduced total sleep time, several night time awakenings, nightmares and non‐restorative sleep .…”
Section: Neurosteroids Are Involved In the Neurobehavioural Effects Omentioning
confidence: 99%
“…Further highlighting the relevance of sleep loss in psychosis and mania, recent research has shown that acute SD may serve as a proxy paradigm to study these conditions . Indeed, acute SD results in psychotomimetic states, with perceptual distortions, anhedonia and cognitive disorganisation; furthermore, SD leads to a rapid elevation of mood and exacerbation of manic symptoms . Sleep loss is also associated with greater severity symptoms in Tourette's syndrome, obsessive compulsive disorder, and PTSD .…”
Section: Neurosteroids Are Involved In the Neurobehavioural Effects Omentioning
confidence: 99%
“…Once stable, however, many women desire to breastfeed. Patients should be advised that sleep deprivation due to breastfeeding may impact recovery (14) and alternate arrangements for nighttime feedings may be helpful. While no longer officially contraindicated by the American Academy of Pediatrics, breastfeeding during lithium treatment remains controversial.…”
mentioning
confidence: 99%